Analysis of vertical drifts in the post sunset equatorial F-region during geomagnetically quiet and disturbed periods - Simi, K.G.; Vineeth, C.; Pant, T.K.; Alex, S. (My University, 2013)
This paper reports the HF Doppler Radar measured post sunset F-region vertical drift (Vd) over Trivandrum (8.5°N, 77°E, 0.5°N dip latitude) during quiet and disturbed periods. In general, Vd showed significant day-to-day variability, both in the overall trend and the nature of short period oscillations present. Analysis based on the simultaneous measurements of equatorial electrojet (EEJ) induced surface magnetic field (ΔH) and interplanetary magnetic field (IMF) revealed that the Vd, on geomagnetically quiet days, exhibit oscillations of periodicity 15-20 minutes; whereas on disturbed days, it exhibit a dominant oscillation of ~ 45 minutes periodicity, similar to the one present in the IMF. Overall, the vertical drifts during quiet days seemed to be controlled by gravity waves of lower atmospheric origin. On the other hand, during disturbed time, the vertical drift is controlled by the interplanetary medium through the coupled electric field. It has also been observed that whenever post sunset Vd showed enhanced oscillation of 15-20 minutes periodicity, the equatorial spread-F occurred.
Keywords: Equatorial ionosphere; Equatorial electrojet (EEJ); Equatorial magnetic field; Interplanetary magnetic field (IMF); Auroral electrojet